Clinical and Genetic Analysis of CHD7 Expands the Genotype and Phenotype of CHARGE Syndrome - Qin, Zailong; Su, Jiasun; Li, Mengting; Yang, Qi; Yi, Shang; Zheng, Haiyang; Zhang, Qiang; Chen, Fei; Yi, Sheng; Lu, Weiliang; Li, Wei; Huang, Limei; et al. (Frontiers in Genetics, 2020)
CHARGE syndrome is a life-threatening disease caused by mutations of chromodomain helicase DNA-binding protein 7 gene (CHD7). The disease is characterized by a pattern of congenital anomalies that involve in multiple organs. In this study, five patients were diagnosed as CHARGE syndrome with CHD7 mutations by whole exome sequencing. Although the clinical phenotypes of probands are highly variable and typical symptoms such as coloboma and choanal atresia are not commonly manifested in this cohort, they all presented congenital heart defects. Of note, dyspnea is the most prominent symptom in all five neonatal patients, suggesting that dyspnea might be a phenotypic clue of CHARGE syndrome.